PECULIARITIES OF USING OF HYDRAULIC DRIVE IN PIPE ROLLING - V. I. Timoshpolskij; D. N. Andrianov (Литьë и металлургия)
In the article there is given the overview of possibility of the devices with hydraulic drive application in pipe rolling. There are shown the advantages of such type of drives as compared to the mechanical and electric ones.